POTENSI PENGEMBANGAN BISNIS MAKANAN TRADISIONAL ROTI KOMPIANG SEBAGAI MAKANAN LEGENDARIS KOTA SOLO - Anggarani , Asih; Hidayat, Herlin; Dyah Hapsari, Yudith (Jurnal Manajemen, 2023)
Efforts to improve the regional economy can be made from various sectors, one of which is the culinary tourism sector. Kompiang as one of the legendary traditional culinary from Solo needs to be preserved because Kompiang Solo produced by Hari Hariyono is the only one in Solo, even Central Java. The development of Kompiang Solo is not as good as the development of Kompiang from Surabaya, Bali, and NTT. Kompiang Manggarai was successfully developed to become a typical souvenir food from NTT. The research aims to analyze the production process, marketing strategy, and regeneration efforts of the traditional food business of Kompiang Cake. This research will conduct a SWOT analysis of the kompiang cake business so that the results of the analysis can be useful for kue kompiang cake entrepreneurs to find out the potential strengths, weaknesses, business and development opportunities, and threats to the kompiang business company in the future. Thus, entrepreneurs will be able to determine the right strategy and business development according to the times for the sustainability of their business. The research will be conducted using primary data obtained directly by observing the Kompiang cake-making location in Solo, in-depth interviews with Kompiang cake entrepreneurs, interviews with the Solo City Government, distributing questionnaires to consumers, and documentation. The results obtained show that Kompiang Solo has the potential to be developed into a typical Solo souvenir food by innovating, in taste, texture, packaging, and service.